Nonlinear time series and principal component analyses: Potential diagnostic tools for COVID-19 auscultation. (November 2020) - Raj, Vimal; Renjini, A.; Swapna, M.S.; Sreejyothi, S.; Sankararaman, S.
Highlights: Development of a potential diagnostic tool for COVID-19 auscultation. Proposes cost-effective digital auscultation based on mathematical techniques. Investigates spectral features of normal – vesicular and bronchial breath sounds. Nonlinear time series and fractal analyses unwrap airflow dynamics in lungs. The principal component analysis helps in classifying the lung sounds. Abstract: The development of novel digital auscultation techniques has become highly significant in the context of the outburst of the pandemic COVID 19. The present work reports the spectral, nonlinear time series, fractal, and complexity analysis of vesicular (VB) and bronchial (BB) breath signals. The analysis is carried out with 37 breath sound signals. The spectral analysis brings out the signatures of VB and BB through the power spectral density plot and wavelet scalogram. The dynamics of airflow through the respiratory tract during VB and BB are investigated using the nonlinear time series and complexity analyses in terms of the phase portrait, fractal dimension, Hurst exponent, and sample entropy. The higher degree of chaoticity in BB relative to VB is unwrapped through the maximal Lyapunov exponent. The principal component analysis helps in classifying VB and BB sound signals through the feature extraction from the power spectral density data. The method proposed in the present work is simple, cost-effective, and sensitive, with a far-reaching potential of addressing and diagnosing the current issue of COVID 19 through lung auscultation.